2019
DOI: 10.26434/chemrxiv.10279751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and Styrene Copolymerization of Novel Fluoro and Oxy Ring-Disubstituted Isopropyl Phenylcyanoacrylates

Abstract: _________________________________________________________________________ AbstractNovel fluoro and oxy ring-disubstituted isopropyl phenylcyanoacrylates, RPhCH=C(CN)CO2CH(CH3)2 (where R is 2-fluoro-3-methoxy, 2-fluoro-4-methoxy, 2fluoro-5-methoxy, 2-fluoro-6-methoxy, 3-fluoro-4-methoxy, 4-fluoro-3-methoxy, 5-fluoro-2-methoxy, 4-fluoro-3-phenoxy) were prepared and copolymerized with styrene. The monomers were synthesized by the piperidine catalyzed Knoevenagel condensation of ringsubstituted benzaldehydes and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 17.2 and 28.2 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of phenoxy ring-substituted phenylcyanoacrylates [18][19][20][21][22][23][24][25][26][27][28][29]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 17.2 and 28.2 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of phenoxy ring-substituted phenylcyanoacrylates [18][19][20][21][22][23][24][25][26][27][28][29]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 20.1 and 45.5 mol% of OPCA is present in the copolymers prepared at ST/ OPCA = 3 (mol), which is indicative of relatively high reactivity of the OPCA monomers towards ST radical which is typical of ring-substituted OPCA [18][19][20][21][22][23][24][25][26]. Since OPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated OPCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Opca Copolymersmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [16][17][18] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization of a number of fluoro, methyl and methoxy ring-disubstituted methyl [19], ethyl [20], propyl [21][22][23], isopropyl [24,25], butyl [26][27], isobutyl [28,29], and 2-methoxyethyl [30] PCAs.…”
mentioning
confidence: 99%
“…4-Fluoro-2-methylphenyl 1methylethyl [3], and 2-methylpropyl [4] PCAs are prepared and copolymerized with styrene. 4-Fluoro-3-phenoxyphenyl methyl [5], ethyl [6], propyl [7], and 1-methylethyl [8], similarly to 4-chlorophenoxy)phenyl 1,1-dimethylethyl [9], 4-(4-fluorophenoxy) phenyl] butyl [10], and 3-phenoxyphenyl 1,1-dimethylethyl [11] PCAs are used as comonomers in radical copolymerization. [1][2][3][4]…”
Section: Introductionmentioning
confidence: 99%